Optimizing research on large-aperture parabolic trough condenser using two kinds of absorber tubes with reflector at 500 °C. (December 2021) - Gong, Jing-hu; Huang, Ji; Hu, Xiaojian; Wang, Jun; Lund, Peter D.; Gao, Caiyun
Abstract: Increasing the aperture of the parabolic trough concentrator (PTC) can effectively reduce costs and help promote. This paper proposed a circle and semicircle absorber tubes (AT) with a flat reflector (FR) in it for the large-aperture PTC system and the size of the AT was determined for the PTC with 8 m aperture width and 80° half rim-angle. The result shown the PTC system using a semi-circular AT with a diameter of 100 mm has the highest average thermal efficiency of 71.6% with DNI 400–1000 W/m 2 at about 500 °Cand has best uniformity of 38.8%. However, its deformation is highest and 1.7 and 1.6 times other two ATs. Therefore, how to reduce the deflection has become a research direction in the future. Currently, the circular AT with a diameter of 80 mm is the most practical with an average thermal efficiency of 69.1% and a minimum deflection.